Differences between Depression and Paranoia: The Role of Emotional Memories, Shame and Subordination - Pinto-Gouveia, José (2014)
The present study explores how emotional memories, shame and submissive behaviour in adulthood are differently related to depression and paranoia, in a sample of 255 subjects from the general community population. Results show that emotional memories (especially, shame traumatic memory) are significantly correlated with external and internal shame. Emotional memories are significantly associated with submissive behaviour. Both types of shame are correlated with submissive behaviour, particularly internal shame. Emotional memories, external and internal shame are linked to depressive symptoms. Emotional memories, external and internal shame, and submissive behaviour are significantly related to paranoia. Path analysis results suggested that (1) shame traumatic memory and recall of threat and submissiveness in childhood predicted depressive symptoms through external and internal shame; (2) early emotional memories of shame, threat and submissiveness predicted paranoid ideation both directly and indirectly, through external shame; and (3) emotional memories impact on paranoid ideation both through their effect upon external shame and also through their indirect effect upon submission, which in turn fully mediates the effect of internal shame upon paranoid ideation. These findings highlight the differences between depression and paranoia. In depression, it is the internalization of early experiences of shame, threat and submissiveness that heighten the vulnerability to depressive states. In paranoia, not only shame traumas and recollections of threat and submissiveness directly influence paranoid beliefs but also these memories promote external and internal shame thoughts and feelings and submissive defenses, which in turn increase paranoid ideation.